Steady State Stability Analysis of Power System under Various Fault Conditions (Global Journals of Research in Engineering, 2011)
Stability is an important constraint in power system operation and control. Power system stability is understood as the ability to regain an equilibrium state after being subjected to a physical disturbance. This paper presents steady state stability analysis of power system and its behavior in accordance with the locations of fault. Principal among these are the determination of system stability on the consideration of Eigen values in steady state condition. This provides appropriate strategy to have a quick decision on the system#x2019;s steady state behavior. The simulation results show the severity of fault and help to make a quick decision that whether it is possible to get the system in normal operation or not.
Keywords: Power system; stability; infinite bus; Eigen value; power system stabilizer (PSS); MATLAB